Nasionalisme Hamka - Muhammad Ridwan; Deddy Ilyas (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Buya Hamka is a charismatic cleric, literary, and also a great and famous politician in Indonesia, his thoughts related to the adoration for the country and the protection of the country are phenomenally evoking the spirit of nationalism in Indonesia which is very burning the spirit of the fighters, And in this study, researchers had the opportunity to find out how buya hamka nationalism is in the book of Al-Azhar Tafsir and focus on verses related to the love of the homeland and the defense of the country. This research uses the maudhu'i interpretation approach where the data obtained is derived from books or study texts relevant to the subject matter. The study also uses an analysis system, in which the author collects verses related to the problems formulated as follows, The first, how Hamka view of nationalism love the homeland and defend the country and the second how hamka nationalism views affect the interpretation of Al-Azhar especially in interpreting the verses of the Qur'an about the love of the homeland and the defense of the state. The results of this study concluded that according to Buya Hamka the country as a means that will be able to maintain religion, if there is no state, religion will have difficulty developing, therefore defending the country and love of the homeland is the same as defending religion and love for religion next is about morals that, A ummah is lived by the value of the life of the ummah itself, by rising or collapsing morals and lastly Buya Hamka said in protecting the existence of the existence of the nation the need for strong faith as a milestone in defending the interests of the nation.